Penggunaan Bahasa Gaul Dalam Pembelajaran Teks Ulasan Melalui Model Talking Stick Pada Siswa Kelas VIII SMP Negeri 2 Sungguminasa - Yunus, Ashar; Azis, Azis; Hasriani, Hasriani (Fakultas Teknik Universitas Negeri Makassar, 2024)
This research aims to describe the form and function of slang in review text learning through talking stick model for students of grade VIII SMP Negeri 2 Sungguminasa. This research used descriptive qualitative method. The population in this study were all VIII grade students of SMP Negeri 2 Sungguminasa including four classes. The data collection in this research used observation, interview, and simak catatat method. The data that has been collected in the form of student and teacher conversations in class VIII SMP Negeri 2 Sungguminasa in learning review texts on the application of the talking stick model is then analysed qualitatively. The results showed that the forms of slang used by the students of grade VIII SMP Negeri 2 Sungguminasa in the learning process of review texts that apply the talking stick learning model are acronyms, contractions, and the use of foreign/regional languages. Meanwhile, the function of slang is expression and familiarity whose use and placement are based on the right situation. The function of expression is not only through oral but must also be followed by body language that describes the speaker's feelings such as happy, sad, angry, surprised, afraid, and so on.